A thematic analysis of factors influencing recruitment to maternal and perinatal trials - Middleton Philippa F; Tooher Rebecca L; Crowther Caroline A (BMC, 2008)
Abstract Background Recruitment of eligible participants remains one of the biggest challenges to successful completion of randomised controlled trials (RCTs). Only one third of trials recruit on time, often requiring a lengthy extension to the recruitment period. We identified factors influencing recruitment success and potentially effective recruitment strategies. Methods We searched MEDLINE and EMBASE from 1966 to December Week 2, 2006, the Cochrane Library Methodology Register in December 2006, and hand searched reference lists for studies of any design which focused on recruitment to maternal/perinatal trials, or if no studies of maternal or perinatal research could be identified, other areas of healthcare. Studies of nurses' and midwives' attitudes to research were included as none specifically about trials were located. We synthesised the data narratively, using a basic thematic analysis, with themes derived from the literature and after discussion between the authors. Results Around half of the included papers (29/53) were specific to maternal and perinatal healthcare. Only one study was identified which focused on factors for maternal and perinatal clinicians and only seven studies considered recruitment strategies specific to perinatal research. Themes included: participant assessment of risk; recruitment process; participant understanding of research; patient characteristics; clinician attitudes to research and trials; protocol issues; and institutional or organisational issues. While no reliable evidence base for strategies to enhance recruitment was identified in any of the review studies, four maternal/perinatal primary studies suggest that specialised recruitment staff, mass mailings, physician referrals and strategies targeting minority women may increase recruitment. However these findings may only be applicable to the particular trials and settings studied. Conclusion Although factors reported by both participants and clinicians which influence recruitment were quite consistent across the included studies, studies comparing different recruitment strategies were largely missing. Trials of different recruitment strategies could be embedded in large multicentre RCTs, with strategies tailored to the factors specific to the trial and institution.